Endoscopic Access to the Ventral Thoracic spine: PETD vs. Thoracoscopy - Jun Ho Lee (Indoscholar, 2018)
Symptomatic thoracic disc herniation (TDH) is estimated to afflict between 1 in 1,000 and 1 in 1,000,000 people; affecting men more frequently than women, with the highest incidence seen at 40-50 years of age. TDH occurs at all levels of the thoracic spine but 75% of cases occur below T8, with T11-T12 being the most common site due to spinal mobility and weakness of the posterior longitudinal ligament. Manipulation of the thoracic spinal cord through the conventional posterior approach has been associated with poor outcomes. A conventional posterior approach consisting of laminectomy, cord retraction, and disc removal was historically done to treat TDH but this causes spinal cord injury and irreversible paraplegia due to cord manipulation on the relatively rigid spinal cord.The anterior approach to the spine is also intimidating to the spine surgeon due to the unique anatomy of the thoracic spine. Conventional open approaches to the thoracic spine involve a thoracotomy, rib resection, and corpectomy to view the spinal cord anteriorly. This has been associated with perioperative morbidity due to surgical site pain, difficult/painful breathing, shoulder girdle dysfunction, and wound healing problems. In order to spare the patients suffering from these postoperative iatrogenic sequelae, the author presents two different minimally invasive approach techniques; percutaneous endoscopic thoracic discectomy (PETD) vs. thoracoscopy, each applied to a different indication or thoracic pathology, to gain an enough but safe access to the ventral thoracic spinal canal through minimized surgical damages without yielding a postsurgical morbidity.